MANASI: A JOURNEY THROUGH POETRY (1294-1297) - Sau, Sudipta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the research paper under discussion, Rabindranath Tagore's poetry collection 'Manasi' is explored. Specifically, this study delves into the poet's inner world and the thematic diversity of his poems over a period of roughly three years. It seeks to determine whether there is a central theme in the Manasi collection. Did, as Pramatha Chaudhuri suggested, feelings of 'despair' and 'resignation' emerge strongly throughout these poems? Research has been conducted to address questions like these. Preliminary investigation suggests that Manasi does not possess a singular central tone. Rather, the poet expresses various feelings toward different events, yet this immediacy does not undermine the unity or lyricism of the poetry. Alongside the artistic success of the poems, one can glimpse hints of the poet's inner turbulence. These aspects—investigation, evidence, and conclusions—will be systematically examined in this research paper.